Financial Analysis in Hong Kong : Qualitative Examination of Financial Statements (2nd edition) for CEOs and Board Members - Kwok, Benny K. B. (Book collections on Project MUSE., 2013)
Financial statements facilitate the communication between corporations and various stakeholders. The integrity, stability and transparency of such communication help preserving Hong Kong as a top global financial centre.To many laypersons, looking through financial statements can be like reading novels in a foreign language, with a sea of jargon obscuring the statements' true meaning. Financial Analysis in Hong Kong 2nd Edition is a product of experience, feedback and chapter review as well as an update of the changes in practices, guidelines, standards and legislations since its 1st edition in 2008. This 2nd edition provides a clear, concise reference for analysing corporations' financial statements.Based on the evaluations of published financials, this book is a convenient standalone guide for both novices and financial professionals in the boardroom and beyond.